Female reproductive tactics in a sex-role reversed pipefish: scanning for male quality and number - Silva, K. (2012)
Theoretical studies predict that females should invest in current reproduction according to both the expected payoffs from mating with different-quality males and their future mating prospects. The Syngnathidae family, with its male pregnancy together with the occurrence of varying degrees of sex-role reversal, constitutes an exceptional model to study female allocation strategies. The present work tests for the influence of male availability and quality (translated into body size) on the egg allocation pattern of different-sized females of the sex role–reversed pipefish Syngnathus abaster. Besides revealing a multiple mating strategy and showing that females do not produce enough eggs to fully occupy a male’s brood pouch during the extent of a pregnancy, results reveal a complex pattern with different-sized females adopting different investment tactics. In contrast to small, less attractive females, who show a much more constant reproductive effort through the tested mating contexts, large females seem able to monitor the number and quality of available males responding accordingly by 1) laying more eggs in the presence of several large males or saving efforts for future breeding and 2) laying larger eggs in larger males while depositing smaller ones in lower quality individuals as a consequence of a serial mating process (large males first, small males later).